Cerebral blood flow evaluation of intensive rosuvastatin therapy in stroke/transient ischemic attack patients with intracranial arterial atherosclerotic stenosis study: Rationale and design. Issue 6 (28th April 2017) - Zhang, Xuting; Zhou, Ying; Zhang, Sheng; Ding, Wenhong; Lou, Min
Abstract: Introduction: The risk of recurrent stroke is high in patients with intracranial atherosclerotic stenosis (ICAS). Statin use has been demonstrated to decrease the incidence of stroke by reducing atherosclerotic plaque burden. However, its effect on the hemodynamic situation and cerebral perfusion status has not yet been validated. With the use of computed tomography perfusion (CTP), we aim to evaluate the impact of Rosuvastatin on cerebral hemodynamic changes, as well as the downstream perfusion. Method: Cerebral bood flow evaluation of intensive rosuvastatin therapy in patients with intracranial arterial atherosclerotic stenosis (CEIRIS) is a single‐center, prospective, randomized, parallel‐group, and open‐label trial, and it will include 50 participants as estimated. Patients with moderate to severe (50%–99%) ICAS are randomized 1:1 to 10 mg/day or 20 mg/day Rosuvastatin and followed every 13 weeks until 52 weeks. The primary outcome for the trial is the change in the relative regional cerebral blood flow evaluated by CTP after 52 weeks of Rosuvastatin treatment. The secondary outcomes are cerebral blood volume, change in the degree of stenosis of the target vessel and lipid parameters. Conclusion: The CEIRIS trial about the effects of statin on the temporal hemodynamic progression of ICAS may extend our understanding of the basic pathophysiology and mechanisms of stroke in ICAS patients. Abstract : With the use of computed tomography perfusion, we aim to evaluate the impact of Rosuvastatin on cerebral hemodynamic changes, as well as the downstream perfusion. This trial concerning the effects of statin on the temporal hemodynamic progression of intracranial atherosclerotic stenosis (ICAS) may extend our understanding of the basic pathophysiology and mechanisms of stroke in ICAS patients.